LAYANAN BIMBINGAN PRANIKAH DALAM MEMINIMALISIR ANGKA PERCERAIAN DI KUA KECAMATAN GENTENG - Indriana; Saifullah (Konseling At-Tawazun, 2024)
Marriage is a sacred bond between husband and wife. Getting married makes a person’s life more focused, peaceful, calm and happy. The aim of this research is to describe premarital guidance services in minimizing the divorce rate in KUA Kec. District roof tiles Banyuwangi. This research uses a qualitative research method with a case study type of research. The results of the premarital guidance research carried out included two services, the first was a regular, premarital guidance service, the second was an independent guidance service where there were only mentors and prospective husband and wife couples, it was carried out at moment rafa’. The material presented by the counselors in the implementation of premarital guidance is about the meaning of marriage, how to achieve a sakinah, mawaddah, warahmah family, communication patterns, the rights and obligations of husband and wife.